Hak Suaka versus Kedaulatan: Studi Kasus Pencari Suaka Etnis Rohingya - B. Lora Christyanti (Badan Penelitian dan Pengembangan Hukum dan HAM, 2022)
The right to asylum is a fundamental right under international law. Despite its fundamental nature, there are still numerous challenges to protect this right. The main challenge is sovereignty, which is the primary basis for the state in determining the one permitted to live on its own territory. The complicacy that the Rohingya underwent in seeking asylum in other countriesis clear evidence of this problem. Rohingya isrecognized as one of the world’s most persecuted minorities, grappling with decades of systematic atrocities. This paper aims to take a closer look at the problems of the right to asylum by answering questions about the challenges Rohingya faced. The study was conducted by juridical method to investigate the right of asylum problems through the experience of the Rohingya. As a result, the Rohingyas encounter a number of challenges in seeking and enjoying their right to asylum. These include denial of access to cross borders, forced deportation, denial of access to procedures to verify refugee status, use of voluntary repatriation as a pretext for withdrawing asylum, use of legal means to expel asylum seekers, and use of non-entre’e mechanisms.